Retrospective evaluation of the impact of functional immunotoxicity testing on pesticide hazard identification and risk assessment. (May 2014) - Gehen, Sean C.; Blacker, Ann M.; Boverhof, Darrell R.; Hanley, Thomas R.; Hastings, Charles E.; Ladics, Gregory S.; Lu, Haitian; O'Neal, Fredrick O.
Abstract Conduct of a T-cell-dependent antibody response (TDAR) assay in rodents according to Environmental Protection Agency (EPA) Test Guideline OPPTS 870.7800 is now required for chemical pesticide active ingredients registered in the United States. To assess potential regulatory impact, a retrospective analysis was developed using TDAR tests conducted on 78 pesticide chemicals from 46 separate chemical classes. The objective of the retrospective analysis was to examine the frequency of positive responses and determine the potential for the TDAR to yield lower endpoints than those utilized to calculate reference doses (RfDs). A reduction in the TDAR response was observed at only the high-dose level in five studies, while it was unaltered in the remaining studies. Importantly, for all 78 pesticide chemicals, the TDAR no-observed-adverse-effect levels (TDAR NOAELs) were greater than the NOAELS currently in use as risk assessment endpoints. The TDAR NOAELs were higher than the current EPA-selected endpoints for the chronic RfD, short-term, intermediate and long-term exposure scenarios by 3–27, 000, 3–1, 688, 3–1, 688 and 4.9–1, 688 times, respectively. Based on this analysis, conduct of the TDAR assay had minimal impact on hazard identification and did not impact human health risk assessments for the pesticides included in this evaluation. These data strongly support employment of alternative approaches including initial weight-of-evidence analysis for immunotoxic potential prior to conducting functional immunotoxicity testing for pesticide active ingredients.